Comparison of the UBC ELISA test and the BTA Trak test for the detection of bladder tumor recurrence: Primerjava občutljivosti urinskih testov UBC ELISA in BTA Trak pri odkrivanju ponovitev tumorjev mehurja - Hajdinjak, Tine; Modrič, Evgenija (Acta Medico-Biotechnica, 2021)
Purpose: To compare the sensitivity of the established BTA Trak™ test with the newer UBC ELISA™ test for the detection of bladder tumor recurrence.Methods: Urine samples from 63 patients were collected prior to cystoscopy. In cases of positive cystoscopy findings, patients were scheduled for TUR and the histologic findings were correlated with the urine test results.Results: There was a statistically significant increase in median UBC value with increasing tumor grade. Median UBC values (µg/L) for tumor stages were: 22.1, 47.5, 95.7 and >150 for pTa, pT1, pT2/3 and CIS, respectively. The overall sensitivity of the UBC and BTA was 62% and 90% (p=0.0049). Comparing different tumor stages, the sensitivity for the UBC vs. BTA was 52% vs.86% (p=0.022) in pTa, 56% vs. 100% (p=0.039) in pT1, 83% for both tests in pT2/3 and 100% for both in CIS. In low grade tumors, the sensitivity of the UBC vs. BTA was 47% vs. 84% (p=0.022); in high grade tumors it was 75% vs. 95% (NS - p=0.085). The combination of both tests did not increase sensitivity over BTA alone. Overall specificity for the UBC was 71% and for the BTA 50% (NS). Overall test accuracy for the UBC 65% was and for the BTA 75% (NS).Conclusion: The UBC ELISA™ test in its present form did not have better sensitivity than the BTA Trak™ test because of its lower validity in low grade/stage tumors.
Keywords: Urinary bladder neoplasms; urine; tumor markers; bladder tumor associated antigen; sensitivity and specificity